Diseño de una intervención para el fortalecimiento de la capacidad organizacional local para la prevención de la enfermedad cardiovascular en Colombia (2020)
Organizational bildong capacity is a public health strategy that helps to improve the management of health organizations, which are the institutions in charge of carrying out actions for the prevention of CVD in municipalities. Therefore, this document is a study on the identification of inputs for the design of an intervention that strengthens the capacity of local health secretariats for the prevention of CVD in Colombia, since, until the information investigated, in Colombia they have designed interventions for this purpose. To identify the inputs for the intervention design, the health planning methodology of Wight, Wimbush, Jepson & Doi (2015) was used, which proposes a series of steps to follow to design an intervention. One of the main findings was to identify that the dimensions of partnerships, human resources and leadership must be modified to strengthen capacity. Another result was to create the intervention change model, which indicates the change mechanisms that would be used to strengthen organizational capacity. Based on the findings, it was shown that the success of the CVD prevention actions created by the ministries are subject to different external and internal factors. Taking the above into account, it is recommended to carry out studies related to the development and strengthening of the capacity of the secretariats at the national level, in order to validate the knowledge found.--Taken from the Degree Document Format.